1983
DOI: 10.1111/j.1532-5415.1983.tb05117.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Cadexomer Iodine in Decubitus Ulcers

Abstract: Thirty-four patients with decubitus ulcers were studied in a randomized trial to compare topical cadexomer iodine with the standard decubitus ulcer treatments used in the participating hospitals. There was a significant reduction of ulcer area with both treatments within three weeks; however, eight of 16 patients treated with cadexomer iodine had a reduction of ulcer area of more than 50 per cent, compared with one of 18 patients treated with the standard treatment (P less than 0.01). Twenty-seven patients con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 10 publications
1
36
0
Order By: Relevance
“…Similarly, iodine-containing compounds have long been used in wound healing but there have been some concerns with toxicity of iodine-containing compounds, especially over large wound areas. For limited wounds, though, cadexomer iodine (iodine within a starch lattice formed into microbeads) has a good deal of data supporting its use as a cost-effective adjuvant for wound healing [27, 28]. …”
Section: Wound Infectionsmentioning
confidence: 99%
“…Similarly, iodine-containing compounds have long been used in wound healing but there have been some concerns with toxicity of iodine-containing compounds, especially over large wound areas. For limited wounds, though, cadexomer iodine (iodine within a starch lattice formed into microbeads) has a good deal of data supporting its use as a cost-effective adjuvant for wound healing [27, 28]. …”
Section: Wound Infectionsmentioning
confidence: 99%
“…Several studies have found that CI is an effective debriding and antiseptic agent for chronic wounds, such as venous leg ulcers 60–65. When CI is used as a dressing, it removes pus, debris, and wound exudates from wounds and reduces bacterial counts 66.…”
Section: Starch‐based Wound Dressingsmentioning
confidence: 99%
“…Several types of topical formulations have been recommended for PrU prophylaxis or treatment. Topical formulations of zinc sulphate , aluminium hydroxide , oxyquinoline , cadexomer , phenytoin solution , ointment of live yeast cell derivative , cream of barley extract , vitamin A ointment , topical insulin and dialysate have been demonstrated to accelerate the wound healing process. In addition, wound environment modulators such as protease‐modulating matrix and acute wound factors such as recombinant platelet‐derived growth factor , nerve growth factor , transforming growth factor beta , granulocyte‐macrophage colony‐stimulating factor and fibroblast growth factor accelerate the healing process of pressure wounds and offer great promise.…”
Section: Discussionmentioning
confidence: 99%